Integrasi Metode Reba Dan Gotrak Dalam Evaluasi Risiko Ergonomi Pada Pekerja Umkm Pindang Bandeng Cicinde - Nana Rahdiana; Ade Suhara; Amallia; Louwis Perdian Sahat Marihot; Kezia Yanfahira Shafa (Jurnal Industri Samudra, 2026)
Manual work activities in the traditional food processing industry have the potential for high ergonomic risks owing to unergonomic work postures, repetitive movements, and the use of work facilities that do not comply with ergonomic principles. This study aimed to evaluate ergonomic risks in milkfish MSME workers through the integration of the Occupational Musculoskeletal Disorders (GOTRAK) questionnaire based on SNI 9011:2021 and the Rapid Entire Body Assessment (REBA) method. This study used a quantitative descriptive approach with a cross-sectional design. Data collection was carried out through observation of work activities, interviews, documentation, filling out GOTRAK questionnaires, and work posture analysis using the REBA method on 12 milkfish MSME workers. The research results show that the majority of workers experience musculoskeletal complaints in the neck (67%), waist (83%), arms (67%), calves (58%), and feet (75%) due to repetitive work activities and awkward position. The results of the work posture analysis showed that fish seasoning activities had the highest level of ergonomic risk, with a REBA score of 9, which is included in the high-risk category and requires immediate corrective action. The research results are also based on the research results, efforts are needed to improve ergonomics by adjusting work facilities, improving work posture, and proposing the use of sit-stand chairs for increasing comfort and reducing musculoskeletal disorders in milkfish MSME workers.